2005
DOI: 10.1111/j.1472-765x.2005.01717.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and pectate-lyase activity of the ruminal bacterium Lachnospira multiparus in the presence of short-chain organic acids

Abstract: Aims: Acetic, propionic, butyric and lactic acids are end products of feed fermentation by rumen microbes. The effects of these short chain acids on growth and pectate-lyase (PL) activity of Lachnospira multiparus were studied. Methods and Results: The bacterial strain used was L. multiparus D32. Acids were tested between 50 and 300 mmol l )1 . Growth and PL activity were measured by the increase in total protein content and by the increase in absorbance at 235 nm in the reaction medium respectively. With the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The present study also showed that the family Lachnospiraceae (genus Lachnospira , phylum Firmicutes) tended to be positively associated with propionic acid ( p < 0.01), while butyric acid did not reach significance ( p = 0.10), suggesting possible divergence in bacteria producing these SCFAs. Indeed, the production of propionic and butyric acids by the same bacterium is unusual [60]. Propionate can also be produced by microbiota from phylum Bacteroidetes [61], but we did not detect this association.…”
Section: Discussionmentioning
confidence: 62%
“…The present study also showed that the family Lachnospiraceae (genus Lachnospira , phylum Firmicutes) tended to be positively associated with propionic acid ( p < 0.01), while butyric acid did not reach significance ( p = 0.10), suggesting possible divergence in bacteria producing these SCFAs. Indeed, the production of propionic and butyric acids by the same bacterium is unusual [60]. Propionate can also be produced by microbiota from phylum Bacteroidetes [61], but we did not detect this association.…”
Section: Discussionmentioning
confidence: 62%
“…Many Lachnospira strains produce butyrate, which plays a crucial role in the maintenance of human gut health [40]. These bacteria produce short-chain fatty acids, which can act as anti-in ammatory agents [40]. This may explain how Tibetans with a low dietary ber intake maintain gut health.…”
Section: Discussionmentioning
confidence: 99%
“…Prevotella mainly participates in the metabolism of carbohydrates and plant proteins as well as short-chain fatty acid production [39]. Many Lachnospira strains produce butyrate, which plays a crucial role in the maintenance of human gut health [40]. These bacteria produce short-chain fatty acids, which can act as anti-in ammatory agents [40].…”
Section: Discussionmentioning
confidence: 99%
“…Many Lachnospira strains produce butyrate, which plays a crucial role in the maintenance of human gut health [40]. These bacteria produce short-chain fatty acids, which can act as anti-in ammatory agents [40]. It may explain how Tibetans with a low dietary ber intake maintain gut health.…”
Section: Discussionmentioning
confidence: 99%